Regional Disparities in Ageing and Longevity in Nepal: A Comprehensive Analysis by Province and Ecological Zone (Okhaldhunga Journal, 2026)
The current demographic transition in Nepal is characterized by low fertility and increasing life expectancy rates, which result in a very fast aging population. This paper discusses the trend in population aging and disparities involving regional and gender differences in both survival and life expectancy and its implications for social and health policy. The analysis is based on census data of 1952/54, 1991, and 2021 to give estimates of the percentage and growth of older adults (60+ in 1991 and 65+ in 2021), dependency rates, aging indices, survival rates, and remaining life expectancy by ecological zone and province. The descriptive statistical techniques are applied to examine the long-term trends and spatial inequalities. Results show that the percentage of older adults grew from 5.0 percent in 1952/54 to 10.2 percent in 2021, which is higher than the national average. The indicators of ageing differ greatly by the provinces; women always have higher survival and life expectancy than men. This paper presents a geographically disaggregated observation of the aging population in Nepal and suggests the necessity to implement equity-based and differentiated social and health protection measures.